Letter from Viktor Homburger to Max Bredig, February 26, 1939 - Homburger, Viktor (1939)
Letter from Viktor Homburger (1888-1968) to Max Albert Bredig (1902-1977). Viktor tells Max that he is waiting for his children to go to England via Kindertransport. Viktor and Marianne Homburger (1903-1986) plan to obtain visas and join their children as soon as possible.
Keywords: Homburger, Marianne, 1903-1986; Bredig, Max Albert, 1902-1977; Homburger, Viktor, 1888-1968; World War (1939-1945); Kindertransports (Rescue operations); Third Reich